2019
DOI: 10.2993/0278-0771-39.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Early Red Abalone Shell Middens, Human Subsistence, and Environmental Change on California's Northern Channel Islands

Abstract: Red abalone (Haliots rufescens) shell middens, a distinctive site type on the California Coast dating primarily to the Middle Holocene, provide important insight into human-environmental interactions and climatic and environmental change. Despite decades of research and debate about why red abalone middens formed and how they relate to past human behavior and environmental change, significant questions persist about the nature of these sites and how they relate to broader trends in human diet and land use. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Red abalone, Haliotis rufescens , are an invaluable resource that have been used by Native coastal Californians ( Rick et al 2019 ) and have been commercially and recreationally harvested along the West coast of the United States ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Red abalone, Haliotis rufescens , are an invaluable resource that have been used by Native coastal Californians ( Rick et al 2019 ) and have been commercially and recreationally harvested along the West coast of the United States ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Erlandson [19] revisited these midden sites in the early 1990s, collected radiocarbon ( 14 C) samples, and demonstrated that all contained Early Holocene components dated between~9300 and 7700 cal BP. The youngest of these was a patchy red abalone shell midden at CA-SRI-26 found in a buried paleosol~1-1.5 m below the surface [20,21]. In deeply incised gullies nearby, multiple paleosols were visible deeper in Late Pleistocene alluvial sediments of the Upper Tecolote Formation, but no archaeological materials were found in these older soils at the time (Fig 2).…”
Section: Plos Onementioning
confidence: 99%